Analysis of Foveal and Parafoveal Microvascular Density and Retinal Vessel Caliber Alteration in Inactive Graves’ Ophthalmopathy - Cetin Akpolat; Muhammed M. Kurt; Merve Yılmaz; Fikriye Ordulu; Ferhat Evliyaoglu (Journal of Ophthalmology)
Purpose. We aimed to evaluate foveal and parafoveal density using optical coherence tomography angiography and the alteration on the retinal vessel diameter in patients with inactive Graves’ ophthalmopathy compared to age-matched normal population. Materials and Methods. Patients with inactive Graves’ ophthalmopathy (study group) and healthy individuals (control group) were enrolled in the cross sectionally designed study. The optical coherence tomography angiography parameters and retinal vessel diameter measurements were assessed between the study and control groups. Foveal and parafoveal microvascular density in the retina was measured using optical coherence tomography angiography. Retinal artery and vein diameter and artery/vein ratio were assessed for retinal vessel caliber changes. Results. Patients with inactive Graves’ ophthalmopathy had higher values of intraocular pressure, proptosis, and axial length (P=0.001, P=0.002, and P=0.008, respectively). Temporal parafoveal vessel density was 48.93 ± 3.21 and 47.62 ± 2.59 in the study and control groups, respectively (P=0.017). Nasal parafoveal vessel density was 47.55 ± 3.01 and 46.46 ± 2.57 in the study and control groups, respectively (P=0.035). Foveal, superior, and inferior parafoveal vessel density values were similar in the study and control groups (P=0.268, P=0.107, and P=0.055, respectively). Patients in the study group had narrower retinal artery and vein diameters (P≤0.001 and P=0.033). Artery/vein ratio was significantly higher in the control group (P≤0.001). Conclusion. Optical coherence tomography angiography could be a novel and promising noninvasive diagnostic technique in patients with inactive Graves’ ophthalmopathy to detect foveal and parafoveal vessel density changes compared to healthy subjects. The decrease of retinal vessel diameter might be observed in patients with inactive graves ophthalmopathy.